SYSTEM FOR MANAGING EXTERNAL SERVICES IN THE MAIN MAINTENANCE OF INDUSTRIAL EQUIPAMENT - Gonzaga Pereira, Otacilio Romulo; Amorim de Araujo, Yuri; Rodrigues de Oliveira, Everton (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
This work addresses the management of external services in industrial maintenance, emphasizing the control and traceability of components throughout the repair process. The proposal is to analyze the implementation of digital tools in processes that are currently conducted manually, enhancing the tracking of parts sent for external service and making the process more organized, efficient, and aligned with the technological advances of Industry 4.0. In this context, the use of technologies such as applications cloud computing allows for more efficient monitoring and planning, facilitating rapid decision-making. These applications improve maintenance management by providing a more efficient approach that aligns with technological advances.